Color Atlas of Emergency Trauma - Demetriades, Demetrios, 1951-; Chudnofsky, Carl R.; Benjamin, Elizabeth R. (Cambridge University Press, 2021)
"The purpose of this atlas is not to replace traditional textbooks, but like so much of educational content delivery today it strives to bring it alive with graphics, key points that are critical to a learner's understanding, and refine a subtle point in diagnosis or treatment. The experience this atlas offers is unparalleled given the legacy of Dr. Demetriades. Dr. Demetriades' personal contribution has spanned over 30 years caring for trauma patients. The authors highlight pearls of wisdom that can keep people out of trouble. Images and content have been selected with an eye toward modern educational principles: creating that emotional response to learning that occurs through visual and graphic information"--